Carcinoma of the vagina presenting as a ruptured procidentia with an entero-vaginal fistula and prolapse of the small bowel. Issue 704 (June 1984) - Howat, J. M. T.; Mohandas, I.; Stassan, L.; Daw, E.
Abstract : A case of a carcinoma of the vagina which presented as a ruptured procidentia with an entero-vaginal fistula and prolapse of the small bowel is reported.